Порівняльний огляд методів лінійних матричних нерівностей і H∞-оптимізації щодо задачі пригнічення зовнішніх збурень для стабілізації нестійкого об’єкта - Gorbatyuk, O. D.; Melnik, K. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
The problem of limited modulo external disturbances suppression for the stabilization of the helicopter hovering is considered. The solution of the assigned problem is implemented by linear matrix inequalities (LMI) method and H∞-optimization. The Analysis of the obtained results of synthesis is carried out both analytically and with the help of stabilization system modeling in Simulink environment. Interpretation of the obtained results is presented.